Determinants of Capital Structure : An Exclusive Study of Passenger Car Companies in India - Santhosh Kumar, S.; Bindu, C. (Indian Journal of Finance, 2018)
Capital structure decision is one of the core financial decisions in a firm. Theoretically, composition of capital structure has a significant stake in determining the earnings available to equity holders and thereby, the market value of a firm. If it is so, a better understanding about the determinants of capital structure is inevitable to manage the decisions of a firm. This study attempted to identify the determinants of capital structure of passenger cars companies listed on the Bombay Stock Exchange (BSE) of India. The long-term debt to total capital ratio was considered as the dependent variable representing the capital structure. The determinants of capital structure which were considered as the independent variables are : (a) size of the firm, (b) profitability, (c) tangibility, (d) growth in assets, (e) non-debt tax shield, (f) debt service capacity, and (g) dividend payout ratio. A panel regression was run to identify the determinants by following a logical procedure for establishing the relationship. Though the independent variables were sensibly and carefully chosen from the existing literature, none of these determinants were found to have a statistically significant relationship with capital structure in the case of passenger car companies in India. However, the overall F - statistics confirmed that the specified model with the above explanatory variables had more predictability power and could explain more than what the intercept only model could explain.